Information literacy : moving toward sustainability : third European Conference, ECIL 2015, Tallinn, Estonia, October 19-22, 2015, Revised selected papers /: moving toward sustainability : third European Conference, ECIL 2015, Tallinn, Estonia, October 19-22, 2015, Revised selected papers. (2015) - Unknown
No abstract available